Boosting Vocabulary Skills in Young Learners Using Mnemonics and the Fly Swatter Game - Fahira Namsa; Nursalim; Nurteteng (TEKILA: Journal of Language Teaching and Literature, 2024)
Vocabulary acquisition is a cornerstone of language learning, particularly for young learners, as it forms the foundation for effective communication and comprehension. This research aimed to examine the effectiveness of using mnemonic strategies combined with the Fly Swatter game to enhance vocabulary learning among 5th-grade students at SD Muhammadiyah Aimas, Sorong Regency. Vocabulary acquisition is a vital component of language learning, yet many young learners face difficulties in memorization and retention. By incorporating an engaging and interactive teaching method, this study sought to improve both learning outcomes and student motivation. Using a pre-experimental One Group Pre-test Post-test design and a quantitative approach, data were collected from 40 students through vocabulary tests consisting of multiple-choice and matching questions administered before and after the intervention. Statistical analysis revealed a significant improvement, with average scores increasing from 57.5 on the pre-test to 85.8 on the post-test. These results demonstrate that combining mnemonic strategies with interactive games effectively enhances vocabulary learning and retention. The findings underscore the importance of integrating creative teaching methods that foster active participation and create a dynamic learning environment. This approach not only supports better academic performance but also increases student engagement and interest in language learning. Teachers are encouraged to adopt such innovative strategies to address common learning challenges and make vocabulary acquisition more effective and enjoyable.